Effect of Scaling Factor in Ground Motion Selection of Seismic Analysis and Design of RC Moment Frame Structures - Thaw, Thiri; Ornthammarath, Teraphan (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 25, 2020)
Selection and Scaling of ground motion plays a major role in designing the structural analysis since the collected data will be applied as seismic load to the structure. Spectrum matching to a smooth target spectrum with the specific input parameters of the scenario; magnitude and source-to-site-distance are focused; is considered in the research. Target spectrum is selected by using the ASCE code guideline. The paper includes three analysis procedures (1) Equivalent lateral force, (2) Response spectrum analysis and; (3) Time history analysis; are applied to the structures which are multi-degree-of-freedom structures with different fundamental periods of vibrations. Seven sets of ground motion suites are collected based on different scale factor ranges from PEER-NGA website. Using scale factor more than limit 4, effect the lateral displacement demand of the structural analysis which lead to bias in some cases. This study indicated that using scale factor less than 1 tend to underestimate the structural response and more cracking than the limit 4 tend to overestimate the demand which is not convenient in practice.